1999
DOI: 10.1200/jco.1999.17.10.3207
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Cardiac Mortality Among 15-Year Survivors of Cancer Diagnosed During Childhood or Adolescence

Abstract: Fifteen-year survivors of childhood cancer have excess mortality. More effective treatments must be developed to reduce this excess risk. Fifteen-year relapse-free survivors did not have excess mortality. This group will require continued observation to determine whether excess mortality will become apparent as more events occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
44
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(51 citation statements)
references
References 35 publications
4
44
0
2
Order By: Relevance
“…[10][11][12] Previous studies have found elevated risks for chronic health conditions which contribute to higher mortality among survivors of childhood cancer patients compared to the general population. 5,9,13,14 Patterns of increased excess mortality after childhood cancer have been shown to be dependent on time from cancer diagnosis and cause of death. 4,7,11 The success of improved cancer survival is overshadowed by the life-threatening chronic health outcomes that cancer survivors are more likely to suffer from.…”
mentioning
confidence: 99%
“…[10][11][12] Previous studies have found elevated risks for chronic health conditions which contribute to higher mortality among survivors of childhood cancer patients compared to the general population. 5,9,13,14 Patterns of increased excess mortality after childhood cancer have been shown to be dependent on time from cancer diagnosis and cause of death. 4,7,11 The success of improved cancer survival is overshadowed by the life-threatening chronic health outcomes that cancer survivors are more likely to suffer from.…”
mentioning
confidence: 99%
“…In children heart and lung disorders are one of the three main causes of death [8]. The recurrence of primary disease and secondary malignancies are the two most common causes among childhood cancer survivors [9]. Cardiac dysfunction may present as myocardial dysfunction, myocarditis, congestive cardiac failure, arrhythmias, valvular dysfunction and accelerated risk of myocardial dysfunction in later life.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 It is now clear that adult survivors of childhood cancer face excessive cardiovascular morbidity and mortality. [6][7][8][9][10][11][12] The increased cardiovascular morbidity is correlated with several defined risk factors, including cumulative lifetime anthracycline dose, concomitant radiation therapy, the use of other cardiotoxic medications, genetic predispositions, and other as yet incompletely defined factors. In an effort to minimize cardiotoxicity, routine monitoring of individuals treated with these agents is used before, during, and after treatment.…”
Section: Introductionmentioning
confidence: 99%